Optimized Fe-doped ZnO nanoparticles for magneto-opto device applications. (2020) - Rehani, Divya; Bishnoi, Swati; Saxena, Manish; Narain Sharma, Shailesh
Abstract: Magnetic impurity in wide bandgap semiconductors incorporate magneto-electro-optical properties. For the vast application and demand of future market devices; Fe-doped ZnO (Fe-ZnO) powders at different Fe doping concentrations were synthesized by solid-state reaction route. 3%Fe-doped ZnO thin films were also grown using solution route as a powder sample of 3%Fe-ZnO was found to be the Room Temperature Ferromagnetic (RTFM). X-ray Diffraction (XRD) patterns showed the increase in secondary phases from single phase wurtzite ZnO structure with increase in Fe concentration. UV-Vis absorption spectroscopy (UV-Vis) showed decrease in bandgap. In Photoluminescence (PL) spectra quenching is observed as Fe 3+ ions occupies the photogenerated Zn ion with an increase in doping concentration. SEM analysis revealed the spherical morphology of nanoparticles ranges in 50 nm. Agglomerations of the Fe 2+/ Fe 3+ ions leads to paramagnetism with an increase in Fe doping. Vibrating Sample Magnetometer (VSM) showed that only 3%Fe-ZnO sample was found to be RTFM whereas paramagnetic behavior dominates with the increase in Fe doping concentration. Since, the type of synthesis route adopted doesn't have a control of physical and chemical property of any material; Rather the choice of dopant (magnetic-Fe) and the host (optical-ZnO) in an optimized ratio can proves to be a single material with magnetic-optical properties. This material as combination of two properties proves to be a potential for spintronic and biosensor-based device applications both in non-medical and medical areas.